Implementasi nilai pancasila: Membangun karakter jiwa pancasila melalui pembelajaran yang interaktif - astuti, dyas fajar (Maliki Interdisciplinary Journal, 2025)
This article aims to look at the development of student character, which is one of the biggest challenges for education from time to time, including in Indonesia. To deal with this issue. The government has included the Strengthening Pancasila Student Profile Project (P5) as the main part of efforts to implement Pancasila values ​​in the character of students and has made this program a main part of the Merdeka curriculum implemented by every school. However, the government has not fully implemented this project (P5) in schools in Indonesia. This research aims to monitor how learning is appropriate and can be implemented at SDN 1 Mulyoagung school as one of the schools that implements (P5) in the Merdeka curriculum. Data collection was carried out by observing the school environment and interviews with the school. This project was declared successful in its implementation of teaching at the school, and the students really accepted this way of learning.